Evaluation of robot-assisted surgery simulation skills after three days of intensive exposure – experience from intensive hands-on training courses - Özkan, Arif; Liakos, Nikolaos; Moritz, Rudolf; Janssen, Martin; Kayaci-Güner, Özlem; Grabbert, Markus; Bründl, Johannes; Ubrig, Burkhard; Siemer, Stefan; Gratzke, Christian; Wagner, Christian (Frontiers in Surgery, 2025)
IntroductionRobot-assisted surgery represents a significant advancement in modern surgical techniques, offering the potential of unparalleled precision, flexibility, and control. Effective training of console surgeons is critical to harness these benefits. Simulation-based training, especially with virtual simulators like the Da Vinci Skills Trainer, plays a pivotal role in developing these essential skills. This study investigates the impact of intensive, short-term hands-on training courses on the simulation skills of robotic surgery trainees in Germany.MethodsWe conducted a retrospective analysis of 52 participants from urological clinics with established robotic programs, who attended intensive training courses organized by the German Society of Robot-assisted Surgery (DGRU) and the Working Group (AK) Laparoscopy and Robot-Assisted Surgery of the German Society of Urology between 2018 and 2022 in a single training centre (IRCAD, Strasbourg, France), guided by experienced teachers. The training program included pre- and post-course evaluations using four specific exercises on the Virtual Reality Simulator (Da Vinci Skills Trainer): Ring Walk, Peg Board, Energy Dissection and Suture Sponge. Performance improvements were analyzed using paired t-tests. Statistically significant difference was considered as p < 0.05.ResultsThe results demonstrated significant improvements in participants’ skills across all evaluated exercises. The mean scores for the Ring Walk increased from 68.9 to 86.68 (p < 0.0001); Peg Board from 75.01 to 92.89 (p < 0.0001); Energy Dissection from 62.29 to 79.42 (p = 0.0377); and Suture Sponge from 61.41 to 79.21 (p < 0.0001). Notably, 78.84% of participants showed improvements in at least three of the four exercises, with an average score increase of 17%.ConclusionIntensive simulation-based training was associated with improvements in robotic surgery simulation scores. These findings suggest that such training programs may help shorten the learning curve for novice surgeons and could contribute to improved readiness for clinical practice.